Relationship between Students' Confidence and Performance in English Speaking Class (Gunung Djati Conference Series, 2025)
This study investigates the relationship between self-confidence and speaking performance among English as a Foreign Language (EFL) students. Utilizing a mixed-method, data were collected through a self-confidence questionnaire and speaking performance assessments from 24 university-level English major students. The analysis categorized students’ confidence levels into low, moderate and high. A total of 9 students (37.5%) fell into the moderate confidence category. Meanwhile, 15 students (62.5%) were categorized as having high self-confidence. Cross-tabulation and Pearson correlation tests were used to analyze the data, revealing a statistically significant positive correlation between self-confidence and speaking performance (r = 0.637, p = 0.001). These findings suggest that students with higher self-confidence tend to perform better in speaking tasks, demonstrating greater fluency, accuracy, and active engagement. Furthermore, the study reinforces previous research that highlights self-confidence as a key determinant of successful oral communication in EFL contexts. The findings underscore the need for EFL educators to foster student self-confidence through supportive teaching practices and meaningful speaking activities, contributing to more effective speaking instruction.